A Periodically Rotating Distributed Forcing of Flow over a Sphere for Drag Reduction - Son, Donggun; Lee, Jungil (Mathematics, 2023)
In the present study, we propose a periodically rotating distributed forcing for turbulent flow over a sphere for its drag reduction. The blowing/suction forcing is applied on a finite slot of the sphere surface near the flow separation, and unsteady sinusoidal forcing velocities are azimuthally distributed on the sphere surface. This forcing profile periodically rotates in the azimuthal direction over time with a forcing frequency, satisfying the instantaneous zero net mass flux. The Reynolds number considered is (Formula presented.) and large eddy simulations are conducted to assess the control performance. It is shown that the drag reduction performance varies with the forcing frequency, and the control results are classified into low-frequency ineffective, effective drag reduction, and high-frequency saturation regimes. With forcing frequencies in the effective drag reduction regime, a helical vortex is generated from the forcing on the sphere and evolves in the shear layer, and this vortex is responsible for the separation delay and flow reattachment resulting in the base pressure recovery and drag reduction. The maximum drag reduction is about 44% with the forcing frequency in the effective drag reduction regime, while controls in other regimes do not produce a drag reduction.
Keywords: active open-loop control; drag reduction; flow control; flow over a sphere; periodically rotating distributed forcing; turbulent flow